If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 6t + 2 Reorder the terms: 8 = 2 + 6t Solving 8 = 2 + 6t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6t' to each side of the equation. 8 + -6t = 2 + 6t + -6t Combine like terms: 6t + -6t = 0 8 + -6t = 2 + 0 8 + -6t = 2 Add '-8' to each side of the equation. 8 + -8 + -6t = 2 + -8 Combine like terms: 8 + -8 = 0 0 + -6t = 2 + -8 -6t = 2 + -8 Combine like terms: 2 + -8 = -6 -6t = -6 Divide each side by '-6'. t = 1 Simplifying t = 1
| 6=2+3 | | 4+11=2 | | 26+2(3x+11)=-18 | | 2n+12=46 | | x-(-5)=-9 | | 23-56= | | 10+7-113=159 | | 3x*3y=168 | | 8a+11=75 | | 8k-8=9k | | 72+5+9=96 | | 6-148+3=68 | | 90+10-3=64 | | 0=x^2-6x+11 | | -19.3-4.2= | | 6x-55+9=14 | | -52.3-12.5= | | 0=x^2-6+11 | | 6ln(x-3)=1 | | 10-3-60=80 | | 3x+3-5x=15+4x | | 11(4x+3)=19 | | 30x^5-32x^4-4x^3-4x^2-14x-2=0 | | 4b+11=19 | | Dx+dy=0 | | 12-6-74=22 | | 5(2h+2)=5h | | 2x+3=2(3x-8) | | 1+4c=-15+8c+48 | | 143+6+8=67 | | 3x+2x-7=18 | | 3(2x-5)+20=-2(x+6) |